Cryptic termites avoid predatory ants by eavesdropping on vibrational cues from their footsteps. (February 2017) - Oberst, Sebastian; Bann, Glen; Lai, Joseph C.S.; Evans, Theodore A.
Abstract: Eavesdropping has evolved in many predator–prey relationships. Communication signals of social species may be particularly vulnerable to eavesdropping, such as pheromones produced by ants, which are predators of termites. Termites communicate mostly by way of substrate‐borne vibrations, which suggest they may be able to eavesdrop, using two possible mechanisms: ant chemicals or ant vibrations. We observed termites foraging within millimetres of ants in the field, suggesting the evolution of specialised detection behaviours. We found the termite Coptotermes acinaciformis detected their major predator, the ant Iridomyrmex purpureus, through thin wood using only vibrational cues from walking, and not chemical signals. Comparison of 16 termite and ant species found the ants‐walking signals were up to 100 times higher than those of termites. Eavesdropping on passive walking signals explains the predator detection and foraging behaviours in this ancient relationship, which may be applicable to many other predator–prey relationships.